How does diabetes mellitus impact on the prognosis of dental implants? - Gabriele Baniulyte (17885981) (2023)
Data sources Web of Science, Embase, PubMed and Cochrane Library databases were searched for publications up to August 2021. Study selection The study noted clear inclusion and exclusion criteria. Search terms were provided; only observational studies were considered. Data extraction and synthesis A total of 122 studies were identified through the search strategy. Following deduplication, two reviewers conducted the screening. Results A total of 21 observational studies were included, involving cohort, case–control, and cross-sectional study designs. A meta-analysis identified increased risk of peri-implantitis in patients with diabetes mellitus and in smokers when compared to non-diabetic subjects and non-smokers. No significant association was found between poor plaque control or periodontal history and peri-implantitis. Conclusions Patients with diabetes mellitus appear to have a higher risk of peri-implantitis. Other Information Published in: Evidence-Based Dentistry License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41432-023-00909-0